Assessment of patient’s knowledge, attitude and practice regarding hypertension - Bollampally, Manasa; Chandershekhar, Preethika; Kumar, Kodishala Pradeep; Surakasula, Aruna; Srikanth, Sharadha; Reddy, T. Rama Mohan (International Journal of Research in Medical Sciences, 2017)
Background: Hypertension is not a disease but it is an important risk factor for cardiovascular complications. Approximately 77.9 million American adults (1 in 3 people) and one billion people worldwide have high blood pressure. Hypertension can be described as the ‘sleeping snake’ which bites when it wakes up. There is need to investigate KAP among the general population which helps in the future development programmes for effective health education The main aim of this study was to assess the patients Knowledge, Attitude and Practice regarding hypertension. Methods: This is a prospective observational study conducted in the In-patient Departments of Gandhi hospital, Secunderabad for a period of 6 months (August 2015 - January 2016) which was approved by institutional ethics committee. A total of 160 hypertensive patients with or without comorbid condition were included. . Adults of age less than 30 years, paediatrics, Pregnant and lactating women were excluded. Patients were selected by simple random sampling method. A suitably designed and validated KAP questionnaire was administered to hypertensive patients. This questionnaire was filled in at face to face interview along with inform consent Statistical analysis was performed using Graph pad prism software version 5. Data was analysed using unpaired t-test. Results: We observed a good score towards knowledge, attitude and poor score towards practice. Conclusions: Our study signifies that patients require support and guidance for practicing better disease management. Clinical activities such as patient counselling, Home Medication Review, Pharmaceutical care program help to increase the patients practice in disease management.